PERBANDINGAN PENGGUNAAN BAHAN PENGHANCUR SECARA INTRAGRANULAR, EKSTRAGRANULAR, DAN KOMBINASINYA - Ahmad Ainurofiq; Nailatul Azizah (Universitas Sebelas Maret, 2016)
Rate of disintegration the tablet is determined by disintegrant position in intragranular or extragranular. Intragranulary granules were disintegrant into their constituent particles, while in extragranulary tablets were disintegrant into granules.This study aims to determine the effectiveness of the addition of materials disintegrant intragranulary, extragranulary, and combination on the disintegration of the tablet with the parameters of physical properties of tablets produced. The tablets were prepared in three formulas based on comparative materials disintegrant variations intragranular and extragranular. Comparison of the three formulas in intragranular and extragranular: F1 (100%: 0%), F2 (75%: 25%), F3 (0%: 100%). Tablet were prepared using wet granulation method with 10% starch binder materials. The resulting granule tested physical properties of granule include: flow time, angle of repose, and tapping. Furthermore, compressed with a constantdepth of punch. The tablets tested the physical properties include: uniformity of weight, hardness, friability, and disintegration time.Statistical results with oneway ANOVA test showed that between tablets formula have difference disintegration time tablet was significant difference with the addition of disintegrant. Data base obtain showed that all formulas parasetamol tablets fulfilled the requirements of granular physical test but only F2 fulfilled the requirements of tablets physical test. The most effective formula tablet is F2 (75%:25%) was disintegration time (8.05 minute).